Pengaruh Kebijakan Dividen dan Kebijakan Utang Terhadap Nilai Perusahaan: Studi Empiris Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2022 - Arif budi hartono; Dewi sukmasari; Mega Metalia; Niken Kusumawardhani (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research aims to find out whether dividend and debt policies have a significant positive effect on the value of pharmaceutical companies listed on the Indonesian stock exchange for the 2017-2022 period. By applying the purposive sampling method, this research selected 8 pharmaceutical companies using a six-year observation method and the total sample obtained was 48 observations. The type of data used in this research is quantitative data and the data source for this research uses secondary data. The data source used in this research is published data from the company’s annual financial reports. The data analysis methods used are descriptive statistical analysis, classical assumption testing, model testing, hypothesis testing. The results of the research show that dividend policy has an effect on company value. Meanwhile, debt policy has no effect on company value.